The relationship of empowering workers with organizational performanceField research of the views of the scientific leaders of a number of colleges at the University of Baghdad - انيس غانم ارزوقي; عباس ياسمين خضير (Journal of Economics and Administrative Sciences, 2011)
The Strategy of employees’ empowerment, organizational performance and total quality management represent three informative which were and still the hub of many studies and researches including the current study. The higher education is considered one of the most important services sectors and the main development as well as the civil progress in the society. It is the main source that provides the organizations with the human resources having scientific or practical professions. So Higher Education has been chosen especially Baghdad University as a sample of the study. The study problem is concentrated to find answers of the following questions: What the level of the powers mandate in the organization concerning the study and how the administrative leaderships understand the empowerment philosophy? Are the organizational performance standards of the interested organization formulated according to individual or collective philosophy by which the work’s vision with team logic is diagnosed? Has the organization concerned with the studying take into account the relation between its organizational performance and the service standards based on empowerment strategy diminutions and how could be measure that? And Were selected a random sample has been chosen from Baghdad University’s colleges to be the study community, while the sample depends on the deans & their assistants and the scientific departments heads for (6) colleges divided into three groups (medical, scientific and humanitarian). The study depends on the analytical survey approach. The research has used a questionnaire which is a tool to collect the information based on the researches and studies concerning the subject matter and depend on the (SPSS) program in the statistical analysis suitable to the study nature. A group of conclusions have been reached by the study determine the relationships features and their nature as well as the influence among the three main study variables.